Antarctic holothuroids from the Bellingshausen Sea, with descriptions of new species (Echinodermata: Holothuroidea) - O’loughlin, P. Mark; Manjón-Cabeza, M. Eugenia; Ruiz, Francina Moya (Zootaxa, 2009)
Three new species of holothuroids from the Antarctic Peninsula and Bellingshausen Sea are described, with O’Loughin & Manjón-Cabeza as authors: dendrochirotids Cucumaria dudexa sp. nov., Psolicrux iuvenilesi sp. nov.; myriotrochid Myriotrochus hesperides sp. nov. Parathyonidium incertum Heding is discussed. Two synonymies for Antarctic holothuroids are formalised: Caespitugo citriformis Gutt is a junior synonym of Thyone scotiae Vaney; Caespitugo diversipes Gutt is a junior synonym of Cucumaria psolidiformis Vaney. Cucumaria armata Vaney is removed from inclusion in the Cucumaria georgiana (Lampert) group, and is a junior synonym of Cucumaria psolidiformis Vaney. A synonymy of Cucumaria aspera Vaney with Psolidium (Cucumaria) coatsi Vaney is rejected; Cucumaria aspera Vaney is referred to the Cucumaria georgiana (Lampert) group. Cucumaria conspicua Vaney is removed from synonymy with Psolidium (Cucumaria) coatsi Vaney, and is a junior synonym of Cucumaria psolidiformis Vaney. Thyone scotiae Vaney is referred to Crucella Gutt. Caespitugo Gutt is a junior synonym of Crucella Gutt. A new genus Cucamba O’Loughlin is erected; Cucumaria psolidiformis Vaney is referred to Cucamba O’Loughlin. A synonymy of Staurocucumis grandis (Vaney) with Staurocucumis turqueti (Vaney) is confirmed. The referral of Pseudocolochirus mollis Ludwig & Heding to Psolidiella Mortensen is confirmed. Lists of contemporary synonymies for Antarctic holothuroid species and generic referrals for Antarctic dendrochirotid species are provided. A table of holothuroid species collected from the Antarctic Peninsula and Bellingshausen Sea by the Spanish BENTART–2003 and BENTART–2006 cruises is provided.